(untitled) (American Journal of Islam and Society, 2016)
This article discusses “Communities of the Qur’an,” a conference, public talk, and forthcoming book that will examine the Qur’an’s “communities of interpretation.” They are represented by ten worldrenowned academics and leaders from the Sunni, Shi‘i, and Ahmadi communities; reformist LGBT, feminist, African American, and Qur’an-only groups; as well as non-Muslims like the Bahais. In this brief paper, I discuss their nature, engagements with the Qur’an as a text or an experience, and the challenges they face in the twentyfirst century.